Preanalytical errors in 24-hour urine collection - Saldaña Orejón, Italo Moisés (2021)
Introduction. Urine collection within 24 hours is necessary for the measurement of biochemical constituents with variable urinary excretion, however, this process is not free of preanalytical errors. Objectives. To evaluate the level of compliance with the instructions for sample collection, identify the collection of incomplete urine and know the pre-analytic processes applied by a group of professionals. Methods. Observational design study, in which anonymous and voluntary surveys were conducted with 257 outpatients and 59 Medical Technologist professionals, in addition to estimating the urinary excretion of creatinine in 416 samples. Results. The study evidenced incorrect collections (39.7%), use of inappropriate containers (58.14%), poor preservation of samples (98.8%), change in fluid intake habits (23.7%), little information and feedback to patients on the preparation of the test, 76.92% of samples presented losses or excesses in the volume collected and a high variability of the criteria used by professionals to reject poorly collected samples. Conclusion. Low compliance of the patients to the indications for sample collection, a high proportion of incomplete collections, and discordance in the preanalytical processes for the 24-hour urinalysis were observed.